Wonder vs. Sublime in Romantic and Postmodern Literature - Mukahal, Iyad (Hungarian Journal of English and American Studies, 2021)
Book review: Economides, Louise. The Ecology of Wonder in Romantic and Postmodern Literature. New York: Palgrave Macmillan, 2016. vii + 214 pages. ISBN 978-1-137-47750-7. E-book. 84.99.